PEMANFAATAN KONTEN MEDIA SOSIAL INSTAGRAM SEBAGAI SARANA PEMBELAJARAN - Ahmad Faisal; Allysa Ramadhanti (Cahaya Ilmu Bangsa, 2025)
Learning media as well as technology are intertwined in today's digital environment. Technology attracts many users, which makes it a useful tool to foster teachers' creativity and make it easier for students to learn. The use of social media as a learning platform is one of the major breakthroughs brought by the rapid advancement of technology, which forces educators to constantly adapt. There are more opportunities to use social media for learning as data shows that Indonesians use the internet and social media more frequently. For example, with features such as IGTV, Reels, and Stories, Instagram which was once intended for sharing pictures and videos now has a lot of potential as an interactive learning tool. This research utilizes library research, which involves gathering information from various relevant scholarly works. This research shows how social media can improve the effectiveness and efficiency of the teaching and learning process if used responsibly. However, inappropriate use can have detrimental effects such as reduced motivation to learn and cyber-dependence. To ensure that learning materials remain current and of interest to students, educators are encouraged to keep coming up with new ideas.